Telling the whole story: Anticipation, inspiration and reputation in a field deployment of TellTable - Cao, Xiang; Lindley, Siân; Helmes, John; Sellen, Abigail (Proceedings of CSCW 2010, 2010)
We present a field study of TellTable, a new storytelling system designed to support creativity and collaboration amongst children. The application was deployed on a multi-touch interactive table in the library of a primary school, where children could use it to create characters and scenery based on elements of the physical world (captured through photography) as well as through drawing. These could then be used to record a story which could be played back. TellTable allowed children to collaborate in devising stories that mixed the physical and the digital in creative ways and that could include themselves as characters. Additionally, the field deployment illustrated how children took inspiration from one another’s stories, how they planned elements of their own tales before using the technology, and how the fact that stories could be accessed in the library led some to become well-known and popular within the school community. The real story here, we argue, needs to take into account all that happens within the wider context of use of this system.